Formic acid oxidation electrocatalyst of palladium nanoparticles synthesised by electroless deposition using various reducing agents - Kwok, Jermyn Tze Rong (2015)
This report details on a newly developed method of synthesising nanoparticle electrocatalysts for fuel cell purposes. It focuses on palladium nanoparticle interactions in formic acid based fuel cells where oxidation is to take place. These nanoparticles are synthesised by coating a glassy carbon electrode via deposition cycles by dipping the electrode into a reducing agent and subsequently into a palladium solution. For this project, 9 deposition cycles was held constant and the reducing agents used were sodium hypophosphite hydrate (NaH2PO2), hydrazine (N2H4), and borane-dimethylamine (DMAB) to form Pd/P, Pd/N2H4, and Pd/B respectively. Due to the relatively new procedure, a lot of trial and error was made into improving the testing method to determine the preferred electrocatalyst for formic acid oxidations. By the end of the project, it was determined that Pd/N2H4 had the lowest specific activity while Pd/P and Pd/B had very similar specific activities.